Why A New Ethical Framework Is Needed To Eliminate Disability Discrimination? A New Learning From The Pandemic - Ranju, Gausul Azam; Serice, Tania (Bangladesh Journal of Bioethics, 2021)
Discrimination between disabled and non-disabled people is still an issue of fairness and justice. In this COVID-19 pandemic time, this issue highlighted in a significant way. In hospital, the disabled persons to face today issues while triage like whether they have the right to get the ventilator first when there is limited ventilation support or their vulnerability could be the cause for being neglect or they do not have to have a quality of life. There are lots of ethical dilemmas that we face today and these are not solvable overnight by the existing framework or policies. The existing paternalism, utilitarianism, or even ableism can not ensure making people living with disabilities (PLWD) rights equal. It is very clear that the professional expertise, policy or framework have so many loop holes that we are still struggling to take steps to effective and ethical decision making. This paper focuses the emergency of ethics based research, policy directions, and frameworks to eliminate those discriminations.